The awakening [compact disc, unabridged] - Chopin, Kate, 1850-1904 (Dreamscape Media, LLC, 2015)
Unsatisfied with the expectations of Creole society and unhappy with her family life, Edna Pontellier begins to fall in love with the dapper Robert Lebrun. Lebrun's flirtations, along with the lifestyle of renowned musician Mademoiselle Reisz, rejuvenates Edna's sense of freedom and independence. However, an affair with the womanizer Alcee Arobin provides Edna with a taste of the danger that comes with living outside of social convention.